Epistemologi Tafsir Nuzuli dan Relevansinya terhadap Metodologi Istinbāṭ Hukum Islam Kontemporer - Slamet Arofik; Eko Andy Saputro (SAMAWAT: JOURNAL OF HADITH AND QURANIC STUDIES, 2025)
The development of contemporary society has given rise to various legal issues that demand a renewal of the methodology of istinbāṭ (derivation) of Islamic law, so that it becomes more responsive to social change without losing its normative foundation. On the other hand, Tafsīr Nuzūlī—an exegetical approach that emphasizes the chronology of revelation and the historical context of the Qur'anic verses—has thus far been studied primarily as a method of Qur'anic interpretation, while its contribution to the development of Islamic legal methodology remains relatively underexplored. This research aims to analyze the epistemological construction of Tafsīr Nuzūlī and to examine its relevance to contemporary Islamic legal istinbāṭ methodology. This study is library-based research (library research) employing approaches from Qur'anic exegesis (tafsīr), Islamic legal theory (Uṣūl al-Fiqh), history, and maqāṣid al-sharī‘ah (objectives of Islamic law). Data were analyzed using content analysis and conceptual analysis methods. The findings indicate that the epistemology of Tafsīr Nuzūlī is built upon an integrative dialectic among the Qur'anic text, the historical context of revelation, reason, and social reality. This epistemological framework is relevant to the development of contemporary Islamic legal istinbāṭ, as it is capable of uncovering legal rationality, identifying Maqāṣid Al-Sharī‘ah, and encouraging the formulation of law that is more contextual and adaptive to societal dynamics. This research offers a maqāṣidī-nuzūlī istinbāṭ model as an integrative approach in the development of contemporary Islamic law.